El método global y su relación con el aprendizaje de la lectoescritura en estudiantes del cuarto ciclo del nivel primario en la IEPS N° 601412 del distrito de San Juan Bautista en el año 2022 - Huayunga Saldaña, Helen Tatiana (2023)
Objective: The aim of this study was to determine the relation between the global method and the learning of read write in students of the fourth cycle of primary school of the IEPS N° 601412 of the district of San Juan Bautista in the year 2022. Materials and methods: It was applied a lickert ordinal scale with 15 items and a quantitative scale to measure read write to 52 students, previous validation for experts. The study was, descriptive – relational and the design was not experimental and transversal. for the statistical analysis we used Tb of Kendall. It was observed that there is a low level of application of the global method and read write. The result of the statistic Tb=0,475; with a significance p=0.00<0.05. Conclusion: There is a significant relationship between the application of the global method and the learning of literacy in students of the fourth cycle of primary school of the IEPS No. 601412 of the district of San Juan Bautista in the year 2022